Trade Policy and Macroeconomic Balance in the World Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The paper explores the relationship between trade policy and current accounts. The effect on the current account of a change in protection at home and then abroad is analyzed, assuming that the exchange rate floats. The 'savings-and-investment approach' is used. It shows that there is no presumption that protection would reduce a deficit. With a fixed exchange rate, the effect on savings and investment is brought about by the reduction in absorption that is required to maintain internal balance when restrictions are imposed. A current account deficit or real appreciation may generate protectionist pressures stimulated by 'conservative resistance.'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet